Awareness Regarding Dangerous Signs in Pregnant Women attending BBH Filter Clinic, Rawalpindi - Tahir, Syed Raza; Khan, Fatima Ali; Mudassar, Tayyaba (Journal of Rawalpindi Medical College, 2025)
Introduction: Maternal health relates to the well-being of a woman during pregnancy, childbirth, and the postpartum period. This study aimed to assess the level of awareness of dangerous signs among pregnant women attending the Filter Clinic in Benazir Bhutto Hospital, Rawalpindi. It was also intended to determine the association of awareness levels among pregnant women during pregnancy with sociodemographic factors and to find out the determinants of awareness of dangerous signs during pregnancy. Materials & Methods: A cross-sectional study was carried out at Benazir Bhutto Hospital filter clinic in Rawalpindi city. A total of 366 pregnant women were selected through non-probability consecutive sampling. Data was collected using a validated tool, Johns Hopkins Program for International Education in Gynaecology and Obstetrics (JHPIEGO’s) (MeSH) Maternal and Neonatal Program. Pearson’s chi-squared test of Independence and binary logistic regression were applied for univariate and multivariate analysis, respectively. Results: Among the 366 respondents, the majority them were in the age bracket of 31-40 years (n= 156). Results of the present study showed that slightly more than half of the respondents reported poor awareness regarding danger signs during pregnancy (n= 190). Moreover, major determinants of awareness level among respondents were the education level of women and monthly family income (p value<0.05). Discussion & Conclusion: The present study indicated that, on the whole, the population revealed somewhat poor awareness regarding dangerous signs. Women’s education and monthly family income play important roles in determining the awareness level among pregnant women regarding dangerous signs. Keywords: Awareness, Pregnancy, Women, Pakistan.